Pemberdayaan Potensi Ekonomi Produktif Masyarakat Berbasis Potensi Desa Melalui Penguatan Lembaga Keuangan Mikro dan Forum Pemberdayaan KeluargaDi Desa Sumberejo Kecamatan Ambulu Kabupaten Jember - Hary Sulaksono; Tamriatin Hidayah; Gatot Sugeng Purwono (RELASI : JURNAL EKONOMI, 2015)
The key issue is KKN-PPM Increased self-financing and self empowerment communities. The purpose of this activity, are: 1. General purpose referring to guide implementation of the Higher Education KKN PPM Kemendikbud, while specific objectives include: a) Increase awareness and empathy of STIE Mandala students related to potency and community issues, b) Addressing the problems in rural communities targeted by the concept of "working with the community " . The establishment of the family empowerment through the forum and strengthening microfinance institutions; c) Develop a work plan to achieve the objectives of KKN-PPM d) Obtaining partners who can work together for the sustainability of KKN-PPM is the Department and related agencies; private or state-owned partners. Method: 1) Phase preparation and debriefing; observation area; 2) Implementation phase, and the identification of potential problems, needs analysis, arrange programs, Implementation of KKN-PPM location, monitoring and evaluation (internal and external), 3) Phase sustainability plan.Implementation of KKN-PPM of Mandala College is the core program (according to the theme of KKN-PPM) and supporting programs  that support the programs of Sumberejo Village . There are 12 LKMM Sumberejo Village, where 5 is ready to be cooperative.Social care by LKMM (prakoperasi) have a positive impact on the environment in hamlets annually provide social support through funding of net income, which can be used for social areas such as education, health, and environment.